2001
DOI: 10.1111/j.0435-3684.2001.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical applications of structuration theory

Abstract: This study reviews and classifies fifty-three potential empirical applications of structuration theory in geography and the social sciences. These were retrieved using a computerized keyword search of articles and books published in the English language between 1982 and 2000. The five dimensions for classifying these studies were (1) a representable type of social behaviour, (2) a methodological bracketing, (3) using specific data, (4) a treatment of time-space, and (5) an interpretation of a duality of struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
9
0
3
Order By: Relevance
“…In 1985 Moss and Dear stated that 'there has been little exploration into the empirical viability of structuration theory for geographic research' (Moss and Dear, 1985: 231) and proposed a model for analysing the structuration of urban space that links spatial form and social relations. Such attempts have however, been, rare, and Phipps (2001) recently concluded that geographical applications of structuration theory have not succeeded in integrating geography with the structuration process, namely in the acknowledgement of the duality of structure. 1 Thus Pred's (1984) views of the application of structuration theory with time-space geography in understanding how places are produced, reproduced and transformed still has yet to be accomplished.…”
Section: Conceptual Embeddingmentioning
confidence: 99%
“…In 1985 Moss and Dear stated that 'there has been little exploration into the empirical viability of structuration theory for geographic research' (Moss and Dear, 1985: 231) and proposed a model for analysing the structuration of urban space that links spatial form and social relations. Such attempts have however, been, rare, and Phipps (2001) recently concluded that geographical applications of structuration theory have not succeeded in integrating geography with the structuration process, namely in the acknowledgement of the duality of structure. 1 Thus Pred's (1984) views of the application of structuration theory with time-space geography in understanding how places are produced, reproduced and transformed still has yet to be accomplished.…”
Section: Conceptual Embeddingmentioning
confidence: 99%
“…(STONES, 2005;POZZEBON;PINSSONEAULT, 2005) Mesmo submetida a essas (e outras críticas), a Teoria da Estruturação tem sido utilizada em trabalhos nas mais diversas áreas como, por exemplo, sistemas contábeis, arqueologia, demografia, cultura organizacional, política, sociologia da tecnologia, gestão de redes interfirmas, estudos migratórios, análises do esporte e lazer, e sobre gênero e patriarcado (BRYANT; JARY, 2001, p. 43-61). Phipps (2001), analisando 53 obras (artigos, livros, capítulos de livros e teses) que empregaram a Teoria da Estruturação empiricamente, também identificou uma gama extensa de áreas e temas, dentre eles, vários estudos relacionados às organizações.…”
Section: Estudos De Perspectiva Estruturacionista: Críticas E Aplicaçõesunclassified
“…A Teoria da Estruturação tem sido utilizada em trabalhos nas mais diversas áreas do conhecimento (BRYANT;JARY, 2001;PHIPPS, 2001). No campo de estudos organizacionais, também é significativo o número de trabalhos desenvolvidos com suporte na Teoria da Estruturação.…”
Section: Introductionunclassified
“…Among the various post-structuralist approaches, one adopted by scholars in many disciplines is structuration theory (Phipps 2001). In its most basic form, structuration theory holds that structure and agency are dual processes that are mutually and continually reproducing.…”
Section: Tourism Geography Social Theory and Structurationmentioning
confidence: 99%